Inhibition of Corneal Neovascularization by Subconjunctival Injection of Fc-Endostatin, a Novel Inhibitor of Angiogenesis - Junko Yoshida; Robert T. Wicks; Andrea I. Zambrano; Betty M. Tyler; Kashi Javaherian; Rachel Grossman; Yassine J. Daoud; Peter Gehlbach; Henry Brem; Walter J. Stark (Journal of Ophthalmology)
We assessed the antiangiogenic effects of subconjunctival injection of Fc-endostatin (FcE) using a human vascular endothelial growth factor-induced rabbit corneal neovascularization model. Angiogenesis was induced in rabbit corneas through intrastromal implantations of VEGF polymer implanted 2 mm from the limbus. NZW rabbits were separated into groups receiving twice weekly subconjunctival injections of either saline; 25 mg/mL bevacizumab; 2 mg/mL FcE; or 20 mg/mL FcE. Corneas were digitally imaged at 5 time points. An angiogenesis index (AI) was calculated (vessel length (mm) × vessel number score) for each observation. All treatment groups showed a significant decrease in the vessel length and AI compared to saline on all observation days (P<0.001). By day 15, FcE 2 inhibited angiogenesis significantly better than FcE 20 (P<0.01). There was no significant difference between FcE 2 and BV, although the values trended towards significantly increased inhibition by BV. BV was a significantly better inhibitor than FcE 20 by day 8 (P<0.01). FcE was safe and significantly inhibited new vessel growth in a rabbit corneal neovascularization model. Lower concentration FcE 2 exhibited better inhibition than FcE 20, consistent with previous FcE studies referencing a biphasic dose-response curve. Additional studies are necessary to further elucidate the efficacy and clinical potential of this novel angiogenesis inhibitor.